Development of a spreadsheet-based solver: Modeling momentum and energy transport in PEMFC cathode - Nurul Raihan Primuharsa Putra (2023)
This thesis is about the development of a spreadsheet-based CFD solver of proton exchange membrane fuel cell (PEMFC) at Cathode. A two-dimensional model of the momentum and energy transport equation were solved using Microsoft Excel. Details of all equations and steps on each cell that were developed are discussed in this report. The Finite Volume Method (FVM), Power Law scheme and Semi-Implicit Method for Pressure-Linked (SIMPLE) Algorithm were applied. The fluid flow was assumed to be incompressible and Laminar value of the Reynolds number was less than 2100. The boundary conditions were set up to be similar for both Microsoft Excel and ANSYS Fluent software for the purpose of comparison. The results from the Microsoft Excel simulation for the velocity and temperature profile were visualized and illustrated in the form of graphs and tabulated data. A grid-independence test was carried out to determine the number of nodes required to give higher accuracy of the result produced. Results from Microsoft Excel and ANSYS Fluent showed the same trend. For this work, the heat generation rate, channel length, velocity inlet and type of fluid were varied. The heat generation rate was varied by 2.5x106 W/m3, 7.5x106 W/m3 and 12.5x106 W/m3. The results showed an increment of temperature by less than 2K from the increment of each heat generation rate. Besides that, the channel length was varied between 0.01 m, 0.02 m, and 0.03 m that gave the result of heat released faster when the length was shorter and vice versa. The velocity inlet was varied by 1.0x10-3 m/s, 1.0x10-2 m/s and 1.0x10-1 m/s which resulted in the increase of velocity outlet as the inlet velocity increased. The comparison was also made by different type of fluid; air and oxygen. The temperature increase by 0.01K from air to oxygen due to higher value of thermal conductivity and specific heat capacity of oxygen. The velocity for air gave faster result compared to oxygen because of the viscosity of oxygen is much lower than air. Thus, the result from the heat generated rate proved that percentage error between both software is less than 1%. This concludes that Microsoft Excel may be used as a CFD solver for engineering problems.